High tibial osteotomy solely for the purpose of return to lifelong sporting activities among elderly patients: A case series study - Ryuichi Nakamura; Masaki Takahashi; Tomoyuki Shimakawa; Kazunari Kuroda; Yasuo Katsuki; Akira Okano (Elsevier, 2020)
Knee osteoarthritis (KOA) is a common joint disease among older individuals, associated with increased mortality rates. The current study was conducted to examine whether open wedge high tibial osteotomy (OWHTO) is an effective treatment for elderly patients with a desire to return to sporting activities (RTS) who do not report inconvenience or pain in activities of daily living. We examined a case series of 9 KOA patients (12 knees) aged 50 or above with a desire for RTS, who underwent HTO. We assessed patients before surgery and 2 years after surgery to evaluate surgical outcomes and RTS. The results revealed that patients' average Japanese Orthopaedic Association score was significantly improved at 2 years after surgery (97.5 ± 4.5), compared with the preoperative score (87.9 ± 7.2; p = 0.008). In addition, the average Tegner activity level score was significantly improved at 2-year follow-up (5.8 ± 1.1) compared with the preoperative score (2.8 ± 1.1; p < 0.001). Eight of nine cases except a marathon runner returned to pre-symptom sporting performance levels. Overall, the current findings suggest that OWHTO provides an appropriate treatment for older KOA patients with a desire for RTS. Keywords: Knee, Osteoarthritis, High tibial osteotomy, Sport